Economic feasibility of household waste minimisation in Dhaka, Bangladesh - Rafia, Afroz; Tudin, Rabaah (Faculty of Economics and Management, Universiti Putra Malaysia, Serdang, Selangor, Malaysi, 2017)
This article examines the economic viability of waste minimization through reuse and recycling in the city of Dhaka, Bangladesh. To achieve the objective of the study, this study carries out the cost-benefit analysis (CBA). The cost-benefit ratio (BCR) of waste minimization is 1.23 which reveals that waste minimization is economically justified and capable of generating. This study shows that minimization of solid waste in the city of Dhaka is not only a social or environmental imperious, an economically feasible mitigation and, therefore, can be a good alternate to conventional options for solid waste management, reducing the amount of waste transported to and unloaded and recovering valuable materials.